Indikasi Relatif Pada Persalinan Dengan Sectio Caesarea - Nur Lathifah; Topan Aditya Rahman; Yulia Safitri (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background: Sectio Caesarea is performed with absolute or relative indications. On the relative indication,vaginal delivery can be accomplished but delivery with cesarean section will be safer for the mother, baby orboth. In the last three years, the number of cesarean delivery in Dr. H. Moch. Ansari Saleh Banjarmasin hasincreased.Purpose: To analyze the relative indications associated with caesarean section delivery.Method: The method of this research use analytical survey with case control approach. The Population ofthis research are all parturient at Dr. H. Moch. Ansari Saleh Hospital Banjarmasin as many as 4776parturient on 2015. Total number of sample cases are 515 sample with total sampling technique and samplecontrol 515 sample with systematic random sampling technique. Data was collected by documentationmaternal registration book technique. Data was analyzed with Chi Square test use (α=0,05).Result: Based on the results, the history of caesarean section (p=0,000;OR=19,529), breech delivery(p=0,000;OR=2,717), macrosomia (p=0,000;OR=24,028) are associated with caesarean section delivery.However, severe preeclampsia (p=0,0260) is not associated with caesarean section delivery.Conclusion: There is a significant association between the history of caesarean section, breech deliveryand macrosomia with caesarean section delivery. While severe preeclampsia is not association withcaesarean section delivery.Keywords: The Relative Indications, Caesarean Section